Diet and trophic niche of the invasive signal crayfish in the first invaded Italian stream ecosystem - Fabio Ercoli (Nature Portfolio, 2021)
Abstract The occurrence of the signal crayfish Pacifastacus leniusculus in the Valla Stream was the first established population of this invasive species recorded in an Italian stream ecosystem. We evaluated the seasonality of diet and trophic niche of invasive signal crayfish in order to estimate the ecological role and effects on native communities of the stream ecosystem. We studied the differences in food source use between sexes, life stages and seasons using carbon and nitrogen stable isotope analyses. To supplement stable isotope analyses, we evaluated food source usage using traditional stomach content analysis. We tested the hypothesis that juveniles have a different diet, showing different trophic niches, compared to adults. Results indicated that signal crayfish adult and juvenile diets mainly rely on macroinvertebrates and periphyton in summer, shifting to mostly periphyton in autumn. Although the two age classes occupied an equivalent trophic niche, juveniles showed slightly different carbon isotope values, suggesting a somewhat ontogenetic shift consistent among seasons. No significant differences were found in adult and juvenile diets between summer and autumn seasons. Our findings suggest that signal crayfish juveniles and adults exhibited seasonal feeding habits, probably due to ecological behaviour rather than food resource availability, and that both are likely to impose similar effects on macroinvertebrate communities in this and similar stream ecosystems.